The model of the ‘perfect man’ in the medieval islamic culture (Journal of Philosophy Culture and Political Science, 2018)
The first socio-political thinker among the Arabic philosophers, Al-Farabi expanded the boundaries of speculation prior to the consideration of human nature, the meaning of his life, his place in the universe, its role in society, the nature of the state association, expressing their dissatisfaction with the Islamic concept of man. In the era of universal domination of the religious worldview approach of blind faith led to the interpretation of the person is fundamentally different from the officially accepted. In contrast to the Islamic concept of a man as a creature among creatures and servant of God, Al-Farabi considered a man in several aspects of his life: as a physical being, as a living being, as the highest natural mixture, as a rational animal, as a civil creature.Key words: Al-Farabi, virtuous city, perfect society, a perfect man, Arab-Muslim culture.